The Contours of Assessment: Considering Aspects that Influence Prediction Performance. Issue 1 (1st January 2022) - Campagna, Michael F.; Hsieh, Ming-Li; Campbell, Christopher M.
ABSTRACT: Actuarial assessments provide standardized scores for use in assigning client risk levels and identifying needs that can be matched with intervention. Drawing from an established theory and findings from tangential justice studies, the current study argues that using standardized instruments to predict recidivism everywhere is potentially problematic because the determination of conviction/incarceration has been shown to vary by jurisdiction and culture. Our exploratory analysis of a standardized assessment finds that when controlling for nation, age, and gender, heterogeneity in effect sizes is significantly reduced. Implications for the field of justice assessment are discussed.